Lived Experiences on Academic Frustration: Teachers and Students Perspective in Fuzhou China - Mengying He; Macaranas Joy (Ilmu Inovasi Nusantara, 2026)
This study explores the lived experiences of academic frustration from the perspectives of both teachers and students in Fuzhou, China, through an extensive literature review. Academic frustration, defined as the psychological distress resulting from unmet academic goals or persistent learning obstacles, has been widely recognized as a critical factor affecting student motivation, emotional well-being, and academic performance. The review examines the cognitive, emotional, and behavioral dimensions of frustration, along with its cultural and contextual influences, particularly within the Chinese educational system shaped by Confucian values, high-stakes examinations, and intense parental expectations. Findings from the reviewed literature highlight how academic frustration manifests uniquely among Chinese students, often compounded by traditional teaching methods and rigid assessment practices. Moreover, the study emphasizes the need for culturally responsive interventions that support emotional regulation, student autonomy, and family involvement. The insights drawn from this review aim to inform future research and practical strategies for managing academic frustration, ultimately promoting healthier learning environments for both students and educators